HISTORICAL AND PEDAGOGICAL PREREQUISITES FOR THE DEVELOPMENT OF PROFILE EDUCATION - Mantulenko, S.V. (Pedagogy of Higher and Secondary Education, 2008)
The article deals with retrospective analysis of profde differentiation’s problem. There is reveals the historico-pedagogical prerequisites for development and formation of profde education.